Use of crystallite-scale features to predict the reactor-scale performance of a three-way catalyst. (31st August 2018) - Rajbala,; Sharma, Abhishek; Bhatia, Divesh
Graphical abstract: Highlights: Predicted experimental data for a three-way catalyst using crystallite-scale features. Incorporated spillover, reverse spillover and direct storage of oxygen. Temperature-dependent surface diffusivity used to predict oxygen storage capacity. Quantified effect of metal-ceria interfacial perimeter on storage and release kinetics. Low values of OSC at low temperatures explained by incomplete catalyst regeneration. Abstract: A model incorporating the geometry features, transport, and reactions at the crystallite scale is developed to predict the features of a three-way catalyst during cyclic lean and rich conditions. The reactions on the metal crystallite, metal-ceria interface, and ceria surface are considered and the coupling between these reactions and the spillover processes is incorporated. The crystallite-scale model is integrated with the reactor-scale model to predict the experimental concentration profiles for CO oxidation. It is shown that the dependence of oxygen surface diffusivity on temperature can be used to predict the experimental data. It is quantitatively shown that in addition to the active surface area, the interfacial perimeter plays a key role in the spillover and reverse spillover processes. In agreement with the reported trends, the model predicts that the incomplete regeneration of the catalyst at low temperatures is responsible for the low values of oxygen storage capacity. A low but consistent evolution of CO2 occurs for low dispersions in contrast to the high amount of CO2 during the initial few seconds of the rich phase for a high dispersion catalyst. Fundamental insights obtained in the present work are expected to be applicable to other catalysts which involve the spillover effects. To the best of our knowledge, a model which incorporates the geometry features, transport phenomenon and reactions at the crystallite scale and its integration to predict the reactor-scale data under flow conditions for a three-way catalyst has not been reported elsewhere.